Retention and remobilization of aged polystyrene (PS) microplastics in a porous medium under wet-dry cycling - Jingya, Xi; Han, Xu; Lingzhi, Yao; Yijia, Sun; Shuyi, Zhao; Qing, Huang; Yan, Li (Frontiers in Environmental Science, 2025)
Understanding the aging processes of microplastics (MPs) and their behavior under dynamic wet-dry cycles is critical for accurate environmental risk assessment, particularly in unsaturated zones. This study investigates the impact of aging on the retention and remobilization dynamics of polystyrene (PS) microplastics in unsaturated porous media. We employed light-aged PS MPs and conducted column experiments using sea sand under multiple wetting-drying cycles. Key physicochemical properties of the MPs were characterized, and their retention and remobilization were quantified by monitoring effluent concentrations.Aging significantly altered MP properties, increasing their surface negative charge and hydrophilicity. Consequently, aging suppressed the remobilization of retained MPs during drying phases. After five cycles, the total retained fraction of aged MPs (76.88%) was consistently higher than that of pristine MPs (72.83%). Remobilization was primarily driven by mobile air-water interfaces (AWI) once water saturation fell below a critical threshold of approximately 0.6. Although aging increased electrostatic repulsion (which hinders retention), it also increased hydrophilicity, which significantly weakened AWI-driven remobilization during drying. This retention-promoting mechanism (reduced AWI remobilization) outweighed the opposing effect of electrostatic repulsion, leading to greater overall retention of aged MPs. This study highlights the complex regulatory role of aging on MP fate and provides critical insights for assessing the environmental risks of aged microplastics in dynamic unsaturated systems.